CIVIL LIABILITY OF THE PRODUCER FOR DAMAGE CAUSED BY A DEFECTIVE PRODUCT - Ivančević, Katarina B (Pravni zapisi, 2013)
The first statute in Europe which regulated liability without fault for damage caused by a defective thing as a separate institute was the Obligation Relations' Act. In the European Community member states the grounds for liability for damage caused by a defective product have differed. Directive 85/374/EC was hence adopted with the aim to harmonise the regulations of the EU member states with regards to this type of liability. The text of this Directive is a compromise balancing the interests of the producers and the consumers in the European Community. Given the doubtless quality of the Obligation Relations' Act, its text was largely taken over by former SFRY countries and was used as a base for adopting new codifications. The paper investigates the manner in which the provisions of the Directive 85/374/EC were transposed into the national laws of former SFRY countries, where special attention is given to comparative solutions. The analysis shows that there are certain differences, that some solutions have both certain advantages and disadvantages, and that the newly adopted regulations are less favourable to the injured party compared to the position that they would have pursuant to the Obligations' Act. In addition, the author has noted certain discrepancies from the EU standards and requirements concerning the implementation of the provisions of the Directive 85/374/EC. The author argues that a better approach is to pass a separate statutes that would harmonise national regulations with the provisions of the above-mentioned Directive rather than then to transpose its provisions in the statute governing obligation relations or consumer protection. The author advocates for the harmonisation of Serbian legislation with the provisions of the Directive 85/374/EC in this manner. Key words: defective product, damage, producer liability, ORA, Directive 85/374/EEC.